Valdosta High School Scrapbook 34, 1984-1985 - Valdosta High School (My University, 1984)
This item is a scrapbook collection detailing events involving Valdosta High School between 1984 and 1985. This is told through newspaper articles and photographs detailing sports primarily looking at Football, Wrestling, and basketball. This football season culminated in the 18th State Championship for Valdosta.
This item contains 1 PDF file with 178 Pages and title page in addition to 90 JPG files
Keywords: Newspapers; Photographs; Scrapbooks; Lowndes County (Ga.)